Influence of the board of directors on discretionary accruals: Evidence from Vietnamese listed companies - Tran Quoc Thinh; Vo Thi Thanh Thuy; Luu Chi Danh; Dang Anh Tuan (Problems and Perspectives in Management, 2022)
In the trend of globalization, profit is always a concern for companies because the competition is increasingly fierce. With accounting tools and policies, managers of companies can perform profit management. The purpose of this paper is to test the influence of the board of directors on the discretionary accruals in Vietnamese listed companies. The paper uses time series of table data. The sample includes 915 observations of 183 Vietnamese non-financial companies in the period from 2016 to 2020. The feasible generalized least squares method is used to test the hypotheses of the research model. The paper uses two foundational theories, including the agency theory and the signaling theory, to explain the discretionary accruals of Vietnamese listed companies. The results show that the independence of the board of directors, the meetings of the board of directors, and the foreigners in the board of directors influence the discretionary accruals in Vietnamese listed companies. Then, the paper proposes some appropriate policies on regulations to control the discretionary accruals in Vietnamese listed companies to improve the quality of accounting information in the context of regional and international economic integration.